2012
DOI: 10.1111/j.1467-8624.2012.01800.x
|View full text |Cite
|
Sign up to set email alerts
|

Mexican‐Origin Youth’s Cultural Orientations and Adjustment: Changes From Early to Late Adolescence

Abstract: Drawing from developmental and cultural adaptation perspectives and using a longitudinal design, this study examined: (a) mean-level changes in Mexican-origin adolescents’ cultural orientations and adjustment from early to late adolescence; and (b) bidirectional associations between cultural orientations and adjustment using a cross-lag panel model. Participants included 246 Mexican-origin, predominantly immigrant families that participated in home interviews and a series of nightly phone calls when target ado… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
102
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
1
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(113 citation statements)
references
References 37 publications
8
102
3
Order By: Relevance
“…Based on past longitudinal work demonstrating increases over time in migrants' mainstream cultural orientation (and related constructs; Brown et al, 2013;Cemalcilar & Falbo, 2008;Stoessel, Titzmann, and Silbereisen, 2012 ), we expected that participants' mainstream cultural orientation would become more positive over the duration of the study. In contrast, and in line with past research's mixed results on longitudinal changes in the heritage orientation (Brown et al, 2013;Cemalcila & Falbo, 2008;Updegraff et al, 2012), we formed no expectation regarding participants' changes over time in their heritage cultural orientation. Importantly, we hypothesized that greater resting RSA shortly after arrival would predict 1 greater increases in mainstream cultural orientation, but not in heritage cultural orientation, while adjusting for trait levels of extraversion, for initial depression and anxiety levels, as well as for age, sex, and body mass index (BMI), which has been shown to be related to RSA (Koenig et al, 2014).…”
Section: Present Studycontrasting
confidence: 52%
See 2 more Smart Citations
“…Based on past longitudinal work demonstrating increases over time in migrants' mainstream cultural orientation (and related constructs; Brown et al, 2013;Cemalcilar & Falbo, 2008;Stoessel, Titzmann, and Silbereisen, 2012 ), we expected that participants' mainstream cultural orientation would become more positive over the duration of the study. In contrast, and in line with past research's mixed results on longitudinal changes in the heritage orientation (Brown et al, 2013;Cemalcila & Falbo, 2008;Updegraff et al, 2012), we formed no expectation regarding participants' changes over time in their heritage cultural orientation. Importantly, we hypothesized that greater resting RSA shortly after arrival would predict 1 greater increases in mainstream cultural orientation, but not in heritage cultural orientation, while adjusting for trait levels of extraversion, for initial depression and anxiety levels, as well as for age, sex, and body mass index (BMI), which has been shown to be related to RSA (Koenig et al, 2014).…”
Section: Present Studycontrasting
confidence: 52%
“…In short, there is a dearth of research on temporal dynamics. The few longitudinal studies published to date suggest that cultural orientations towards both the mainstream and heritage cultures can change over time (e.g., Brown et al, 2013;Kiang, Witkow, & Champagne, 2013;Rogers-Sirin & Gupta, 2012;Schwartz et al, 2013;Updegraff, Umaña-Taylor, McHale, Wheeler, & Perez-Brena, 2012). For example, international students in the US reported higher identification with the mainstream cultural group three and a half months after migration (Cemalcilar & Falbo, 2008).…”
Section: Acculturation Orientations: Temporal Dynamics and Antecedentsmentioning
confidence: 99%
See 1 more Smart Citation
“…First generation Mexican-American adolescents are less likely to show a pattern of higher Mexican orientation and increasing mainstream American orientation compared to second generation (e.g., Knight et al, 2014). However, other studies have found no relation between nativity and acculturation trajectories (e.g., Updegraff et al, 2012). Parental education may also be consequential for predicting adolescent acculturation, with past studies finding that higher parent education was related to greater English competency among Russian Jewish adolescents (Birman & Trickett, 2001).…”
Section: Background Predictors Of Acculturation Trajectoriesmentioning
confidence: 87%
“…Nonetheless, because there are still few longitudinal studies of acculturation (Knight et al, 2012, Updegraff et al, 2012, how acculturation trajectories relate to psychological and social functioning is still "open for debate" (Ward & Geeaert, 2016). Accordingly, in the present study we examined whether trajectory groups varied across positive youth domains related to confidence, competence, and connection (Lerner, 2004): self-esteem, general self-efficacy, academic self-efficacy, GPA, and family cohesion (Fuligni, Tseng, & Lam, 1999;Qin, 2006;Tseng, 2004).…”
Section: Associations With Positive Youth Developmentmentioning
confidence: 99%